Classification of parameters affecting slip safety of limestones. Issue 1 (31st December 2016) - Çoşkun, G.; Sarıışık, Gencay; Sarıışık, A.
Abstract: This study determines the appropriate surface processing techniques for limestone plates. slip resistance, which is required for the slip safety of pedestrians wearing shoes, is one of the most important parameters for the surface processing of limestone plates used as floor covering. The slip resistances of five different limestone plates, each of which have undergone four different surface processes, were determined according to the TS EN 14231 Standard. To define the factors affecting slip resistance, the mineralogical and petrographic characteristics, chemical properties, physico-mechanical properties of five different types of limestone were identified. Statistical analyses were performed to define the relations among these parameters. Slip resistance values on limestone sample plates were found to change considerably depending on both the surface processing techniques applied and the dryness or wetness of the surface along with its physico-mechanical characteristics. Finally, the limestones used in this research were classified according to safety applications with consideration of their slip resistance values.